Alzheimer's disease genetic risk and sleep phenotypes in healthy young men: association with more slow waves and daytime sleepiness. Issue 1 (16th July 2020) - Muto, Vincenzo; Koshmanova, Ekaterina; Ghaemmaghami, Pouya; Jaspar, Mathieu; Meyer, Christelle; Elansary, Mahmoud; Van Egroo, Maxime; Chylinski, Daphne; Berthomier, Christian; Brandewinder, Marie; Mouraux, Charlotte; Schmidt, Christina; et al.
Abstract: Study Objectives: Sleep disturbances and genetic variants have been identified as risk factors for Alzheimer's disease (AD). Our goal was to assess whether genome-wide polygenic risk scores (PRS) for AD associate with sleep phenotypes in young adults, decades before typical AD symptom onset. Methods: We computed whole-genome PRS for AD and extensively phenotyped sleep under different sleep conditions, including baseline sleep, recovery sleep following sleep deprivation, and extended sleep opportunity, in a carefully selected homogenous sample of 363 healthy young men (22.1 years ± 2.7) devoid of sleep and cognitive disorders. Results: AD PRS was associated with more slow-wave energy, that is, the cumulated power in the 0.5–4 Hz EEG band, a marker of sleep need, during habitual sleep and following sleep loss, and potentially with larger slow-wave sleep rebound following sleep deprivation. Furthermore, higher AD PRS was correlated with higher habitual daytime sleepiness. Conclusions: These results imply that sleep features may be associated with AD liability in young adults, when current AD biomarkers are typically negative, and support the notion that quantifying sleep alterations may be useful in assessing the risk for developing AD.